Pengaruh Lingkungan Kerja dan Pelatihan Terhadap Kinerja Pegawai di Disdukcapil Kabupaten Sukoharjo - Muhammad Fadilah; Taufiq Nur Muftiyanto; Khabib Alia Akhmad (Jurnal Pemimpin Bisnis Inovatif, 2024)
This research investigates the impact of work environment and training on the performance of employees at the Suikoharjo Regency Popuilation and Civil Registration Office. All 50 employees of the office constituited the stuidy popuilation. The stuidy employed work environment, training, and employee performance as key variables. Data collection methods incluided observation, interviews, and quiestionnaires, with data analysis conduicted uising SPSS 26. Findings indicate a positive buit insignificant relationship between work environment and employee performance, a positive and significant relationship between training and employee performance, and a combined influience of both work environment and training on employee performance.